2014
DOI: 10.1890/es14-00010.1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of barren‐ground caribou during winter in response to fire

Abstract: Abstract. We investigated the influence of past fires on the large-scale distribution of barren-ground caribou (Rangifer tarandus groenlandicus) in the Northwest Territories, Canada, during winter. We used an information-theoretic approach and data describing fire history, vegetation, and predation risk to develop resource selection functions that explained caribou distribution on early-and late-winter ranges. We evaluated multiple sets of models constructed across years for all caribou (pooled models) and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 55 publications
3
27
0
Order By: Relevance
“…Caribou tend to select mature stands (>40 years old) containing relatively abundant lichen cover (Joly et al 2003) and avoid immature stands, although recent studies have found that there may be more individual variation in the use of these areas than previously thought (Anderson and Johnson 2014), and some individuals may take advantage of these areas for increased vascular forage (Joly et al 2003). Caribou may also use immature stands as habitat for movement (Rickbeil et al 2016) or possibly to reduce predation risk through enhanced visibility (Anderson and Johnson 2014). The effects of fire on caribou winter habitat, and associated avoidance by individuals, extend well beyond the short-term loss of vegetation due to the recovery time of lichen species.…”
Section: Winter Range Conditionsmentioning
confidence: 96%
See 4 more Smart Citations
“…Caribou tend to select mature stands (>40 years old) containing relatively abundant lichen cover (Joly et al 2003) and avoid immature stands, although recent studies have found that there may be more individual variation in the use of these areas than previously thought (Anderson and Johnson 2014), and some individuals may take advantage of these areas for increased vascular forage (Joly et al 2003). Caribou may also use immature stands as habitat for movement (Rickbeil et al 2016) or possibly to reduce predation risk through enhanced visibility (Anderson and Johnson 2014). The effects of fire on caribou winter habitat, and associated avoidance by individuals, extend well beyond the short-term loss of vegetation due to the recovery time of lichen species.…”
Section: Winter Range Conditionsmentioning
confidence: 96%
“…Regardless of whether caribou populations rely on forage species other than lichens in the winter, what is supported by both recent (Joly et al 2009;Anderson and Johnson 2014) and older studies (Scotter 1964) is that during the winter barren-ground caribou select mature forest stands with productive lichen communities and avoid immature and recently burned stands. We believe that it is therefore a reasonable and precautionary approach to consider it likely that the reduction of abundant lichen forage on the winter range, whether through increased fire activity or altered community composition, can lead to negative effects on barren-ground caribou populations through changes in habitat use and behaviour or abundance.…”
Section: Winter Range Conditionsmentioning
confidence: 98%
See 3 more Smart Citations